(untitled) - Danchin, Antoine (Comptes Rendus Biologies)
A brief history of the field shows that the impression of novelty we have today when we talk about synthetic biology is merely the sign of a rapid loss of memory of the events surrounding its creation. The dangers of misuse were identified even before the first experiments, but this has not led to a shared awareness. Building a cell ab initio involves combining a machine (called a chassis by specialists in the field) and a program in the form of synthetic DNA. Only the latter—the program—is the subject of the vast majority of work in the field, and it is there that the risks of misuse appear. Combined with knowledge of the genomic sequence of pathogens, DNA synthesis makes it possible to reconstitute dangerous organisms or even to develop new ways of propagating malicious software. Finally, the lack of thought given to the risk of accidents when laboratories develop gain-of-function experiments that increase the virulence of a pathogen makes a world where this type of experiments is developed particularly dangerous.